Open Quantum Systems Far from Equilibrium - Schaller, Gernot; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This monograph provides graduate students and also professional researchers aiming to understand the dynamics of open quantum systems with a valuable and self-contained toolbox. Special focus is laid on the link between microscopic models and the resulting open-system dynamics. This includes how to derive the celebrated Lindblad master equation without applying the rotating wave approximation. As typical representatives for non-equilibrium configurations it treats systems coupled to multiple reservoirs (including the description of quantum transport), driven systems, and feedback-controlled quantum systems. Each method is illustrated with easy-to-follow examples from recent research. Exercises and short summaries at the end of every chapter enable the reader to approach the frontiers of current research quickly and make the book useful for quick reference.
An Introduction to Master Equations -- Obtaining a Master Equation -- Solving Master Equations -- Multi-Terminal Coupling: Non-Equilibrium Case I -- Direct Bath Coupling: Non-Equilibrium Case II -- Open-Loop Control: Non-Equilibrium Case III -- Closed-Loop Control: Non-Equilibrium Case IV.
Keywords: Physics; Quantum theory; Mathematical physics; Physics; Quantum Physics; Mathematical Methods in Physics; Mathematical Applications in the Physical Sciences; Mathematical Physics